Antimicrobial resistance among group B Streptococcus and Staphylococcus aureus isolates from bovine mastitis in Brazil over 35 years - Dr Tatiana Pinto; Juliana Ribeiro; Dr Laura Oliveira; Leandro Simões; Dr Natalia Costa; Prof José Carlos Pantoja; Prof Renata Rabello; Prof Lucia Teixeira; Prof Ruth Zadoks (International Journal of Infectious Diseases)
Introduction: Group B Streptococcus (GBS) and Staphylococcus aureus (SAU) are leading agents of bovine mastitis in countries ranked as top-milk producers globally, like Brazil. In addition, both bacterial species can also cause infections in humans. The lack of mastitis management programs leads to the unnecessary use of broad-spectrum antibiotics, which fosters the rise of antimicrobial resistance (AMR). Surveillance of AMR in GBS and S. aureus is needed to inform public health risks and control strategies. Methods: Short-read whole genome sequencing was performed with 156 GBS and 135 SAU. AMR genes were identified from the genomes using the SRST2 program. GBS and SAU strains were recovered from bovine milk between 1987-2021 in Brazil. Results: The AMR genes found among the GBS strains were: tet (tetO n=61, 39%; tetM n=37, 24%), erm (ermB n=41, 26%; ermA n=20, 13%), ant(6)-Ia (n=18, 11%) and lnuC (n=1, 1%). Nineteen (12%) GBS strains were multidrug resistant. SAU strains harbored the following AMR genes: norA (n=86, 64%), tet (tet38 n=85, 63%; tetK n=19, 14%; tetL n=2, 1%), blaZ (n=79, 59%), fosB1 (n=44, 32%), ermC (n=4, 3%), msrA (n=2, 1%) and mecA (n=1, <1%). mecA encodes an alternative penicillin-binding protein (PBP2a) that confers high-level resistance to methicillin (methicillin-resistant S. aureus, MRSA). Among all SAU strains, 71% (n=96) were multidrug resistant. Over the years, AMR rates increased in SAU and GBS strains. Conclusion: Most GBS and S. aureus strains are resistant to antibiotics commonly used for treatment (human and veterinary medicine) and growth promotion in Brazil, highlighting the detection of MRSA and clindamycin-resistant GBS strains which are recognized as global public health threats. Thus, long-term surveillance of drug-resistant GBS and SAU strains is needed to guide local farmers and policymakers on CBM control practices, including antibiotic choice.